Overburden stress evolution characteristics and prediction of disasters with across-gully mining - Wang, Hongwei; Jiang, Baolin; Jiao, Jianqiang; Li, Yanjun (Frontiers in Earth Science, 2023)
The coal water co-mining of shallow coal seams in the loess gully area of Northern Shaanxi is affected by the coupling effect of overburden rock structure and topography. The development characteristics of mining fracture are complex and can induce mining and environmental disasters. To predict the disaster formation, taking the 113101 working face of the Kunyuan Coal Mine as the engineering background, numerical simulation, physical similarity simulation experiment, and theoretical analysis methods were used to analyze the mining gully of a shallow coal seam in a loess gully area. Based on the dynamic evolution characteristics of stress at different locations, the formation positions, dynamic development, and evolution processes of various fractures were studied; disaster-causing mechanisms were revealed and comprehensive methods were proposed. The results showed that in across-gully mining, the maximum horizontal compressive stress at the bottom of Gully No. 2 was approximately 20.00 MPa, the maximum horizontal tensile stress of the reverse slope section was approximately 1.50 MPa, the width of the F5 fracture of Gully No. 2 was 46.00 cm, and the elevation difference was up to 52.00 cm. The working face across-gully mining formed tensile fractures in most areas, collapsed fractures at the gully bottom, and extruded fractures in the reverse slope section. The fracture at the gully bottom could easily induce water–sand inrush and roof caving and supports crushing. The slope fracture could also induce a gully-induced landslide. According to the mechanisms and distribution areas of fracture disasters, the disaster areas were divided into water–sand inrush areas at the gully bottom, roof caving and supports crushing areas at the gully bottom and at the base of the slope section, and landslide areas at the upper part of the slope section and reverse slope section. Appropriate prevention and control measures were proposed, such as the upstream interception of surface water, slope reinforcement in the middle and upper part of the downhill section, artificial precracking of the roof in the middle and upper part of the downhill section, and grouting reinforcement at the gully bottom and slope toe of the downhill section. These measures were proven to effectively guarantee the safe and efficient mining efficiency of the working face.